2015
DOI: 10.1542/peds.2014-2379
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized Celiac Disease in Children Presenting for Rheumatology Evaluation

Abstract: BACKGROUND AND OBJECTIVES: Current clinical guidelines do not consider patients with rheumatic conditions to be at high risk for celiac disease (CD) despite numerous reported associations between the two in adults and children. The objective of this study was to evaluate the prevalence of CD among patients presenting for pediatric rheumatology evaluation.METHODS: A total of 2125 patients presenting for initial evaluation by the Division of Pediatric Rheumatology at the Hospital for Special Surgery between June… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…2 On the basis of multiple studies including ours, absence of clinical manifestation or growth failure in JIA patients cannot exclude CD. 3,5 Therefore, patients with rheumatological complaints are considered to be at higher risk for CD. Also, the presence of symptoms such as inadequate response to routine treatments of JIA can raise the suspicion of the CD.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…2 On the basis of multiple studies including ours, absence of clinical manifestation or growth failure in JIA patients cannot exclude CD. 3,5 Therefore, patients with rheumatological complaints are considered to be at higher risk for CD. Also, the presence of symptoms such as inadequate response to routine treatments of JIA can raise the suspicion of the CD.…”
Section: Discussionmentioning
confidence: 99%
“…2 The association between CD and JIA has been reported in some studies and its prevalence is reported at 1%-10%. 3 Therefore, CD should be considered in patients with JIA when unexplained extraarticular symptoms occur. 3 There are still some questions about the association of these diseases; for example, whether CD should be screened in all patients with JIA before initiation of treatment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These manifest in a wide spectrum, including recurrent abdominal pain, vomiting, malabsorption, enteritis, pancreatitis, and others [ 1 – 3 ]. T-cell-induced immune-mediated disease triggered by gluten-containing food ingestion is known to be a cause of celiac disease (CD) among genetically predisposed individuals [ 4 ]. It has diverse clinical presentations, ranging from enteropathy with signs of severe malabsorption to asymptomatic presentation [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%